2004
DOI: 10.1111/j.1360-0443.2004.00763.x
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and safety of naltrexone and acamprosate in the treatment of alcohol dependence: a systematic review

Abstract: Both acamprosate and naltrexone are effective as adjuvant therapies for alcohol dependence in adults. Acamprosate appears to be especially useful in a therapeutic approach targeted at achieving abstinence, whereas naltrexone seems more indicated in programmes geared to controlled consumption. Both drugs are safe and acceptably tolerated but issues of compliance need to be addressed adequately to assure their usefulness in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
152
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 425 publications
(158 citation statements)
references
References 65 publications
3
152
3
Order By: Relevance
“…MOR blockade in the ventral tegmental area inhibits dopamine release following alcohol intake and opioid antagonists reduce alcohol intake in rodents (Mitchell et al 2009). Consistent with this preclinical literature, naltrexone has been shown to have a small‐to‐moderate effect size in reducing alcohol use in some (Garbutt et al 1999; Bouza et al 2004) but not all studies (Krystal et al 2001). In heroin dependence, naltrexone blocks the physiological and psychological effects of heroin (Navaratnam et al 1994; Brewer 2002; Brewer & Streel 2010), preventing relapse, particularly in the early detoxification phase (Foster, Brewer, & Steele 2003).…”
Section: Introductionmentioning
confidence: 62%
“…MOR blockade in the ventral tegmental area inhibits dopamine release following alcohol intake and opioid antagonists reduce alcohol intake in rodents (Mitchell et al 2009). Consistent with this preclinical literature, naltrexone has been shown to have a small‐to‐moderate effect size in reducing alcohol use in some (Garbutt et al 1999; Bouza et al 2004) but not all studies (Krystal et al 2001). In heroin dependence, naltrexone blocks the physiological and psychological effects of heroin (Navaratnam et al 1994; Brewer 2002; Brewer & Streel 2010), preventing relapse, particularly in the early detoxification phase (Foster, Brewer, & Steele 2003).…”
Section: Introductionmentioning
confidence: 62%
“…Research conducted in the 1990s and early 2000s demonstrated superior outcomes for acamprosate relative to placebo (Kiefer et al, 2003;Whitworth et al, 1996) and confi rmed its safety (Carmen et al, 2004). Other research, including an Australian study (Morley et al, 2006;Richardson et al, 2008) and the large U.S.…”
mentioning
confidence: 99%
“…COMBINE Study (Combined Pharmacotherapies and Behavioral Interventions for Alcohol Dependence; Anton et al, 2006;Donovan et al, 2008), did not fi nd improvements in drinking outcomes. Overall, however, meta-analyses of randomized clinical trials show that, relative to placebo, acamprosate improves both the rate and duration of continuous abstinence (Carmen et al, 2004) and may be more benefi cial than naltrexone for these specifi c outcomes (Maisel et al, 2013).…”
mentioning
confidence: 99%
“…However, there is solid evidence today that pharmacological treatments can prolong the time to relapse following cessation of heavy drinking or decrease the number of heavy drinking days (Bouza, Angeles, Munoz & Amate, 2004). Nevertheless, the fact that ethanol interacts with a great number of neurotransmission systems, along with the genetic and individual factors of alcoholic patients, could explain that there is not a single effective treatment for alcohol dependence.…”
Section: Pharmacological Treatments For Alcoholismmentioning
confidence: 97%